Root transcriptional dynamics induced by beneficial rhizobacteria and microbial immune elicitors reveal signatures of adaptation to mutualists - Stringlis, Ioannis A. (Plant J, 2017)
Below ground, microbe‐associated molecular patterns (MAMPs) of root‐associated microbiota can trigger costly defenses at the expense of plant growth. However, beneficial rhizobacteria, such as Pseudomonas simiae WCS417, promote plant growth and induce systemic resistance without being warded off by local root immune responses. To investigate early root responses that facilitate WCS417 to exert its plant‐beneficial functions, we performed time series RNA‐Seq of Arabidopsis roots in response to live WCS417 and compared it with MAMPs flg22(417) (from WCS417), flg22(Pa) (from pathogenic Pseudomonas aeruginosa) and fungal chitin. The MAMP transcriptional responses differed in timing, but displayed a large overlap in gene identity. MAMP‐upregulated genes are enriched for genes with functions in immunity, while downregulated genes are enriched for genes related to growth and development. Although 74% of the transcriptional changes inflicted by live WCS417 overlapped with the flg22(417) profile, WCS417 actively suppressed more than half of the MAMP‐triggered transcriptional responses, possibly to allow the establishment of a mutually beneficial interaction with the host root. Interestingly, the sector of the flg22(417)‐repressed transcriptional network that is not affected by WCS417 has a strong auxin signature. Using auxin response mutant tir1afb2afb3, we demonstrate a dual role for auxin signaling in finely balancing growth‐promoting and defense‐eliciting activities of beneficial microbes in plant roots.